Logistics Cost Calculation of Implementation Warehouse Management System: A Case Study - Kučera, Tomáš (EDP Sciences, 2017)
Warehouse management system can take full advantage of the resources and provide efficient warehousing services. The paper aims to show advantages and disadvantages of the warehouse management system in a chosen enterprise, which is focused on logistics services and transportation. The paper can bring new innovative approach for warehousing and presents how logistics enterprise can reduce logistics costs. This approach includes cost reduction of the establishment, operation and savings in the overall assessment of the implementation of the warehouse management system. The innovative warehouse management system will be demonstrated as the case study, which is classified as a qualitative scientific method, in the chosen logistics enterprise. The paper is based on the research of the world literature, analyses of the internal logistics processes, data and finally enterprise documents. The paper discovers costs related to personnel costs, handling equipment costs and costs for material identification. Implementation of the warehouse management system will reduce overall logistics costs of warehousing and extend the warehouse management system to other parts of the logistics chain.
Kalkulace logistických nákladů implementace warehouse management systému: případová studie
Keywords: logistics cost calculation; warehouse management system; overall logistics costs; internal logistics processes; kalkulace logistických nákladů; warehouse management systém; celkové logistické náklady; interní logistické procesy